2021
DOI: 10.1186/s12879-021-06398-9
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine preferences driving vaccine-decision making of different target groups: a systematic review of choice-based experiments

Abstract: Background Choice-based experiments have been increasingly used to elicit preferences for vaccines and vaccination programs. This study aims to systematically identify and examine choice-based experiments assessing (differences in) vaccine preferences of vaccinees, representatives and health advisors. Methods Five electronic databases were searched on choice-based conjoint analysis studies or discrete choice experiments capturing vaccine preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 83 publications
1
22
0
Order By: Relevance
“…Patients are a special consumer group and have special preferences for medical services. Therefore, many scholars use the conjoint analysis method to study patients' preferences for medical services [ 48 50 ]. In this study, we used conjoint analysis to analyze the demand preferences for different health management services of a population of older adults with VI, to help clinical researchers to formulate appropriate health management strategies for this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are a special consumer group and have special preferences for medical services. Therefore, many scholars use the conjoint analysis method to study patients' preferences for medical services [ 48 50 ]. In this study, we used conjoint analysis to analyze the demand preferences for different health management services of a population of older adults with VI, to help clinical researchers to formulate appropriate health management strategies for this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…They worked on childhood vaccines, Human Papilloma Vaccine, meningococcal vaccine, Hepatitis B vaccine, diphtheria, tetanus vaccine [24]. A systematic review on choice based experiments on vaccine preferences driving vaccine decision making of different target groups reported vaccine effectiveness, vaccine risk, cost and protection duration as the main factors influencing vaccine decision (Diks et al, 2021). These three systematic reviews have findings similar to our findings although they studied preferences for vaccines other than COVID-19 vaccine; high vaccine effectiveness, low risk of side effects and duration of vaccine protection are reported in all three studies as factors influencing preferences.…”
Section: Discussionmentioning
confidence: 99%
“…The primary pathway for the increases in cases and deaths averted from an oral vaccine is through alignment in vaccine delivery modality with patient preferences, thereby increasing vaccination uptake among the currently unvaccinated. The likelihood of this phenomena is backed in the literature as well as market studies, indicating that oral delivery mechanisms are strongly favored over injectables, particularly among the unvaccinated or vaccine hesitant [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…One method for increasing the uptake of vaccination in the U.S. is to offer delivery modalities that conform to patient preferences more so than injectable multi-dose vaccines [11]. Several studies have shown that in the U.S., oral vaccines are considered more desirable by patients and a recent study estimated that an oral vaccine against COVID-19 may increase vaccination rates among the unvaccinated by 32%, a population accounting for 92% of the 5,938,358 hospitalization days, 93% of the 817,829 ICU days, and 93% of the 355,276 mechanical ventilation days observed over the December 2021-February 2022 outbreak [11][12][13][14]. One such oral vaccine delivery platform is the Vector-Adjuvant-Antigen Standardized Technology (VAAST) platform, developed by Vaxart, Inc. [15].…”
Section: Introductionmentioning
confidence: 99%